The (im)possibility of doing research in a low-income country: the case of Mozambique - Griffin, Gabriele; Mendonça, Marta; Bernardo, Ana Bela; Magaua, Natália; Mate, Isália Gabriel; Mapelane, Lenia; Matlombe, Samuel Benjamim; Nota, Juvêncio (Frontiers in Education, 2025)
This article centers on the difficulties of conducting social and life sciences research in a low-income country: Mozambique. It draws on decolonial, professionalization and self-motivation theory to examine, through qualitative, participative, discussion-based, bottom-up research with local informants carried out between December 2024 and February 2025, what factors inhibit the conduct of research in this context. The article suggests that it is less the self-motivation of the informants than contextual factors which make research difficult. These factors include the significant discrepancies between the abstract workload model of a 40-h week and the actual experiences of working as an academic where many professional activities take much more time than imagined in the abstract workload model. Many professional activities are, further, unrecognized in this workload model and, importantly, also unremunerated—important in a context where basic salaries are low and need to be bumped up by additional labor, either within the employing institution or, very commonly, outside. A further factor in making research difficult is sociocultural, a result of the hierarchist, patriarchal culture that prevails and which subordinates women and junior staff such that they are at the beck and call of more senior and male staff who can call on them at any time. This makes the planning of time to conduct research very difficult. All this is compounded by the poor state of the research infrastructure with very limited facilities and intermittent access to the internet, a must in the contemporary knowledge economy. The article ends with a series of recommendations at micro, meso and macro level to remedy this situation.